Effect of timely diagnosis and treatment on growth and body proportionality of children with congenital hypothyroidism - Kochar, Aditya; Kaur, Harvinder; Dayal, Devi (Frontiers in Endocrinology, 2026)
BackgroundCongenital hypothyroidism (CH) is a preventable cause of growth and neurodevelopmental deficits. In India, lack of universal newborn screening (NBS) delays diagnosis. This study examines how treatment timing influences growth, nutrition, and body proportionality in children with CH.MethodsThis cross-sectional study included 66 children with CH, aged under 5 years, receiving Levothyroxine(LT4) therapy for one year. Age and sex-matched 64 healthy children were also enrolled. Children with CH were stratified into early-treated (<3months) and late-treated (>3months) groups. Anthropometric measurements were converted to Z-scores using WHO standards. Body proportionality was assessed using: height–arm span difference, upper segment-to-lower segment (US: LS) ratio, Manouvrier’s Indice Skélique (MIS). MIS classifies skeletal proportions as brachyskelia (short legs, long trunk; score ≤84.9), mesatyskelia (intermediate; 85.0–89.9), and macroskelia (long legs, short trunk; ≥90).ResultsChildren with CH had significantly lower height-for-age (HAZ −2.31 ± 1.32 vs. −0.41 ± 0.96), weight-for-age (WAZ −1.98 ± 1.41 vs. −0.36 ± 1.02), and head circumference-for-age (HCZ −1.52 ± 1.28 vs. −0.21 ± 0.89) Z-scores compared with healthy controls (all p < 0.001). Stunting (HAZ < −2 SD) was present in 53% of children, while underweight (WAZ < −2 SD) was observed in 36.4%. Late-treated children had a higher prevalence of severe stunting (67.7% vs. 11.4%), severe underweight (29.0% vs. 2.9%), and microcephaly (35.5% vs. 8.6%) compared with early-treated children (p < 0.05). Disproportionate stature was observed in 71.0% of late-treated children compared with 42.9% of early-treated children (p < 0.05). US: LS ratio and Manouvrier’s Index further confirmed greater skeletal disproportionality in late-treated children compared with early-treated children (p < 0.05).ConclusionsDelayed treatment in CH significantly impairs growth, increases skeletal disproportionality, and adversely affects neurocranial development. Early initiation of therapy—ideally within the first 3 months—is essential. These findings highlight the need for newborn screening in India.